XRF core-scanning data of composite sediment core ROD11 from the crater basin of Rodderberg, Germany - Zolitschka, Bernd; Frechen, Manfred (PANGAEA, 2025)
XRF core-scanning data characterizes the sediment composition geochemically and supports palaeoclimatic reconstruction of glacial/interglacial cycles for the Middle Pleistocene sediment record from the crater basin of Rodderberg, Germany. A 72.8 m long sediment record was recovered by means of wire-line drilling with 3 m long liners from the silted-up crater basin of Rodderberg (East Eifel Volcanic Field) in the vicinity of the city of Bonn, Germany. The composite record ROD11 was subjected to XRF core scanning with a spatial resolution of 2 mm using an ITRAX XRF core scanner, Cox Analytics with a Molybdenum X-ray tube (Croudace et al., 2019; Croudace and Rothwell, 2015). The measurements were conducted with a fixed setting of 30 kV, 40 mA, and an exposure time of 5 s. The software Q-spec (Cox Analytics) was employed for processing of the scanner output and calculation of qualitative elemental measurements in counts. Principal component analysis was then employed to reduce the data dimension and identify latent environmental control factors for the reliable set of elemental data in the normalized (clr-transformed) and standardized XRF dataset (Bertrand et al., 2024). Valued by multiple dating techniques for the past 430 ka, this terrestrial record provides an environmental reconstruction since the Middle Pleistocene.
Keywords: biogenic silica; carbonates; cluster analysis; crater lake; diatoms; East Eifel Volcanic Field; Germany; grainsize; Interglacials; lake sediment proxies; Magnetic susceptibility; minerogenic matter; organic matter; Palaeoclimate reconstructions; Pleistocene; XRF-core scanning